Book Review: The Islamic Finance Trading Framework; Legitimizing Profit Making - Maliha, Hasna (SMART Insight, 2025)
This article summarizes and analyzes the concept of the Islamic finance trading framework as explained by Mohsin Ali and Najeeb Zada in The Islamic Finance Trading Framework: Legitimizing Profit Making (2019). The book seeks to build theoretical and practical legitimacy for trading and profit-making activities in Islam. Through an elaboration of Islamic commercial law, Shariah financial contracts, and comparison with the conventional system, this work asserts that Islam does not reject profit but places it within the bounds of justice, honesty, and Shariah ethics. Islam transforms the paradigm of profit from merely an economic value into a moral instrument that reflects social responsibility. By rejecting riba, gharar, and maysir, the Islamic trading system presents an economic mechanism that is more stable and just. This model is not only an alternative to conventional capitalism but also offers an ethical foundation that can improve global economic governance.